Testing the 'Residential Rootedness': Hypothesis of Self-Employment for Germany and the UK - Darja Reuschke; Maarten Van Ham (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Based on the notion that entrepreneurship is a 'local event' , the literature argues that selfemployed workers and entrepreneurs are 'rooted' in place. This paper tests the 'residential rootedness'-hypothesis of self-employment by examining for Germany and the UK whether the self-employed are less likely to move or migrate than employees. Using longitudinal data from the German Socio-economic Panel Study (SOEP) and the British Household Panel Survey (BHPS) and accounting for transitions in employment status we found little evidence that the self-employed in Germany and the UK are more rooted in place than employees. Firstly, the self-employed are not less likely to move or migrate over the period 2001-08. Secondly, those who are currently self-employed are also not more likely to have remained in the same place over a period of three years (2008-06 and 2005-03) as compared to those who are currently employed. Thirdly, those who are continuously self-employed are not less likely to have moved or migrated over a 3-period than those in continuous paid employment. Fourthly, in contrast to the prevalent 'residential rootedness'-hypothesis in economic geography and regional studies, we found that the entry into and the exit from selfemployment are associated with internal migration.
Keywords: D22; J61; J62; L26; 330; Self-employment; migration; residential mobility; rootedness hypothesis; UK; Germany; Selbstständige; Unternehmer; Binnenwanderung; Region; Schätzung; Deutschland; Großbritannien